Standalone sauna vs exercise followed by sauna on cardiovascular function in non‐naïve sauna users: A comparison of acute effects - Earric Lee; Joel Kostensalo; Peter Willeit; Setor K. Kunutsor; Tanjaniina Laukkanen; Francesco Zaccardi; Hassan Khan; Jari A. Laukkanen (Health Science Reports, 2021)
Abstract Background and aims Sauna bathing and aerobic exercise have each been shown to affect cardiovascular function. However, direct comparisons between standalone sauna bathing and a combination of exercise and sauna on vascular indices remain limited. Therefore, we conducted a cross‐over study using matched durations to explore the hemodynamic changes of sauna exposure when compared to a combination of aerobic exercise and sauna exposure. Methods Participants (N = 72) with at least one cardiovascular risk factor underwent, on two separate occasions: (a) a 30‐minute sauna at 75°C (SAUNA) and (b) the combination of a 15‐minute cycling exercise at 75% maximum heart rate followed by 15‐minute sauna exposure (EX+SAUNA). Relative changes to arterial stiffness (PWV), augmentation index (Alx), brachial systolic and diastolic blood pressure (SBP and DBP), central SBP (cSBP), mean arterial pressure (MAP), and heart rate (HR) were compared PRE‐POST and pre‐ to 30‐minutes post‐intervention (PRE‐POST30). Results Baseline SBP and DBP were 143 (SD 18) mmHg and 86 (SD 10) mmHg, respectively. From PRE‐POST, SAUNA had lower DBP (mean difference [95% CI] 2.5 [1.0, 4.1], P = .002) and MAP (2.5 [0.6, 4.3], P = .01). However, EX+SAUNA had lower SBP (−2.7 [−4.8, −0.5], P = .02), DBP (−1.8 [−3.3, −0.4], P = .01), and MAP (−2.0 [−3.5, −0.5], P = .009) PRE‐POST30. There were no statistically significant differences between SAUNA and EX+SAUNA for other measured parameters. Conclusion This study demonstrated that when matched for duration, EX+SAUNA and SAUNA elicit comparable acute hemodynamic alterations in middle‐aged participants with cardiovascular risk factors. The sauna is a suitable option for acute blood pressure reductions in those who are unable to perform aerobic exercise, and may be a viable lifestyle treatment option to improve blood pressure control.